The advance on pathophysiological mechanisms of type 2 chronic rhinosinusitis with nasal polyposis - Yang, Cheng; Guo, Ling; Wang, Yuhan; Jiang, Wenjing; Chen, Sijia; Gu, Qingjia (Frontiers in Allergy, 2025)
PurposeThis review aims to explore the pathophysiological mechanisms and emerging therapies for type 2 chronic rhinosinusitis with nasal polyps (CRSwNP), driven primarily by type 2 inflammation.Search methodsA comprehensive search of relevant literature was performed in databases including PubMed, Web of Science, and Scopus, using keywords such as “chronic rhinosinusitis with nasal polyps,” “type 2 inflammation,” “Th2 cells,” “ILC2s,” “epithelial barrier dysfunction,” and “biologics”. The search was limited to articles published from January 2010 to February 2025.Search resultsA total of 200 articles were initially retrieved. After screening based on relevance and quality, 163 articles were selected for this review. These included 109 basic research papers, 30 clinical studies, and 24 review articles.ConclusionsType 2 CRSwNP pathogenesis involves Th2/ILC2-IL-4/IL-13 synergy, driving eosinophilic inflammation and tissue remodeling via a self-amplifying loop. Programmed cell death protein 1 and programmed death-ligand 1 dysregulation intensifies Th2 responses. Epithelial barrier defects (via disrupted junctions and ciliary defects) and epithelial–mesenchymal transition facilitate pathogen invasion and stromal changes. M2 macrophages amplify inflammation via CCL-24 and Staphylococcus aureus synergy, sustaining biofilm persistence. Targeted biologics—dupilumab (IL-4Rα inhibitor) reduces polyp burden and restores smell, while mepolizumab (anti-IL-5) and omalizumab (anti-IgE) address specific endotypes. Despite therapeutic advances, biologics require real-world validation for long-term safety and cost-effectiveness.